2018
DOI: 10.1177/0306419018808746
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative design tools in engineering education: Insight to choose the appropriate PLM software

Abstract: The shift from sequential to concurrent engineering has led to changes in the way design projects are managed. In order to assist designers, many effective tools have been developed to support collaborative engineering. Nowadays, industrial scenarios encourage companies to adopt product lifecycle management solutions, even if they may not be able to understand their benefits. Indeed, product lifecycle management roadmap is quite difficult to implement and return on invest can take time. Moreover, many free sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Furthermore, the variables of the PLM features factor obtained much lower results, except for the role-assignment as a teamwork facilitator, which agrees with the literature as a challenge to overcome since students need to know how to divide work in PLM environments [17]. These low results in PLM features are consistent with previous research that indicates that students prefer to use their asynchronous communication solutions such as SMS [9].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the variables of the PLM features factor obtained much lower results, except for the role-assignment as a teamwork facilitator, which agrees with the literature as a challenge to overcome since students need to know how to divide work in PLM environments [17]. These low results in PLM features are consistent with previous research that indicates that students prefer to use their asynchronous communication solutions such as SMS [9].…”
Section: Discussionsupporting
confidence: 88%
“…However, this system had the following limitation: students could not use simultaneously the same design file. A similar experience took place at the School of Engineering Arts et Metiers ParisTech by combining Catia V5 and Dropbox [17].…”
Section: Introductionmentioning
confidence: 97%
“…We can think, for example, of the distance teaching of Product Lifecycle Management (PLM) in the manufacturing industry, which is often compared to BIM because of the multiple similarities between the two approaches [30,31]. In addition, the academic constraints and the educational context-as summarized by Maranzana et al [32] for PLM education-seem very similar to the issues identified in BIM education in construction [2]. Kakehi et al [33] demonstrated the importance of using practical teaching methods based on case studies in the distance learning environment of PLM.…”
Section: Discussionmentioning
confidence: 99%